1996
DOI: 10.1007/bf00250996
|View full text |Cite
|
Sign up to set email alerts
|

Dietary linolenic acid-mediated increase in vascular prostacyclin formation

Abstract: To define vascular effects of an enhanced dietary alpha-linolenic acid intake, 28 spontaneously hypertensive rats were fed a 3% sunflowerseed oil (44% linoleic acid) diet; in 3 groups (7 rats each), the diet was supplemented with 1, 2.5 or 5% linseed oil containing 62% alpha-linolenic acid. alpha-Linolenic acid was incorporated up to 12% in the aorta of the 5% linseed oil group. The eicosapentaenoic acid content was not significantly increased. The content of arachidonic acid and docosatetraenoic acid was mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Of particular interest are plant oils with a high proportion of α-linolenic acid such as linseed oil (approximately 62%), perilla oil (approximately 54%) and canola oil (approximately 10%). We have shown for the rat that feeding increasing amounts of linseed oil does not increase the content of EPA and DHA in the aorta [65] (Figure 7b). However, the enhanced α-linolenic acid intake reduced the AA level and enhanced production of PGF 1α which is the stable degradation product of prostacyclin.…”
Section: Epa and Dha Conversion From α-Linolenic Acidmentioning
confidence: 83%
See 1 more Smart Citation
“…Of particular interest are plant oils with a high proportion of α-linolenic acid such as linseed oil (approximately 62%), perilla oil (approximately 54%) and canola oil (approximately 10%). We have shown for the rat that feeding increasing amounts of linseed oil does not increase the content of EPA and DHA in the aorta [65] (Figure 7b). However, the enhanced α-linolenic acid intake reduced the AA level and enhanced production of PGF 1α which is the stable degradation product of prostacyclin.…”
Section: Epa and Dha Conversion From α-Linolenic Acidmentioning
confidence: 83%
“…*p < 0.05 versus rats fed a control chow. Data are adapted from [65]. would be the finding that sustained ventricular tachycardia can be reduced by infusion of 3.8 g ω-3 marine triacylglycerols in patients with implanted cardioverter defibrillators [71].…”
Section: Mechanisms Of Antiarrhythmogenic Action Of Epa and Dha Free mentioning
confidence: 99%
“…The content of ALA in the aorta rose by 12% while the concentration of EPA was unaltered. Vascular prostacyclin synthesis increased, resulting in lower blood pressure (Rupp et al, 1996). Apparently, ALA can be converted into EPA and subsequently alters prostanoid production, without raised EPA concentration in cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been suggested that the hypotensive effects of linolenic acid could be mediated through its influence on arachidonic acid and eicosanoids synthesis, leading to an anti-inflammatory response and to vasodilation. 6,9 We used data collected on 4594 white participants of the National Heart, Lung, and Blood Institute (NHLBI) Family Heart Study to assess whether dietary consumption of higher amounts of total linolenic acid (␣-linolenic and ␥-linolenic acid) was associated with a lower prevalence of hypertension and lower resting blood pressure. …”
mentioning
confidence: 99%
“…Animal and human studies on the association between linolenic acid and blood pressure have been inconsistent. Rupp et al 6 showed that a diet supplemented with ␣-linolenic acid lowered systolic blood pressure (SBP) by 6 mm Hg after 7 weeks in 28 spontaneous hypertensive rats. In a crosssectional study of 399 male subjects aged 20 to 78 years, a 1% higher adipose tissue ␣-linolenic acid was associated with a 5 mm Hg lower SBP and diastolic blood pressure (DBP).…”
mentioning
confidence: 99%